Mediation in Social Conflict Resolution at Tanjungpinang Malay Customary Institution, Riau Islands - Syafei, Ermi Suhasti; Habuddin, Ihab; Asrizal , Asrizal; Saputra, Megi (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
This study aimed to examine the strategic role of customary institution in resolving social conflicts in Indonesia through mediation at Tanjungpinang Malay Customary Institution (TMCI). The mediation process was discussed, detailing the reason for selecting TMCI as a mediator, and the role in social conflict theory and normative law. Data were obtained through interviews, observations, and documentation, and literature studies were analyzed using the Miles and Huberman model. The results showed that mediation was implemented systematically and hierarchically by adhering to Malay customs based on Islamic teachings. Furthermore, the community respected and trusted TMCI as a customary institution capable of resolving social conflicts. It also played a strategic role as a party that participated in resolving customary and cultural conflicts and implementing social changes to ensure integration or cohesion. Mediation by TMCI showed that conflict was part of society with groups engaged in both realistic and non-realistic disputes. These groups then integrated and reached a consensus to maintain social cohesion. Regarding normative law, mediation by TMCI was justifiable in Islamic and positive laws.